606 Gender difference in hand grip strength of children in Bosnia and Herzegovina aged 11 to 14 years. A cross - sectional study (Balneo and PRM Research Journal, 2024)
Hand grip strength (HGS) serves as a multifaceted and critical parameter within the domain of motor function and is widely recognized as a pivotal aspect in the comprehensive evaluation of the development of school-aged children. The assessment of hand grip strength transcends its immediate significance as a physical metric; it extends to encompass a broader spectrum of implications encompassing physiological well-being, psychosocial development, and even potential health outcomes. The aim of the research was to determine the values of HGS, the trend of changes and differences between boys and girls, aged 11-14 years from Bosnia and Herzegovina. A cross-sectional survey was conducted on a sample of 585 school children. The subsample was divided into 307 boys (11y = 81; 12y = 87; 13y = 77; 14y = 62) and 278 girls (11y = 66; 12y = 83; 13 y =79; 14y = 50). Hand muscle strength was measured using the method of isometric dynamometry in laboratory conditions, with a standardized test - Hand grip  (according to the American Society of Hand Therapists). The force achieved during the maximum hand grip (dynamometry) was measured with a digital hand dynamometer CAMRY-EH101, USA. Statistically significant differences between male and female respondents were confirmed (for age 12, T = -2.651, p